KADAR HEMOGLOBIN RETIKULOSIT DI ANEMIA DAN NONANEMIA AKIBAT DEFISIENSI BESI ABSOLUT DI GAGAL GINJAL TERMINAL TERKAIT HEMODIALISIS (Reticulocyte Hemoglobin Level of Absolute Iron Deficiency Anemia and NonAbsolute Iron Deficiency Anemia In End State Renal Disease Undergoing Maintenance Hemodialysis) - Amelia Rachmiwatie; Noormartany Noormartany; Rubin Surachno Gondodiputro; Delita Prihatni (Indonesian Association of Clinical Pathologist and Medical laboratory, 2014)
Absolute Iron Deficiency Anemia (IDA) is one of the complications in the End State Renal Disease (ESRD) patients undergoingmaintenance hemodalysis, with an incidence of 76.4%. If this condition is not properly addressed, it can lead to impaired cardiac functionand increased mortality. The incidence of this case is between 30−45%. The determination of the iron status in ESRD patients wqs setby the Perhimpunan Nefrologi Indonesia 2011 using serum ferritin and transferrin saturation, but they do not provide a meaningfulchange in the value of the initial state of the iron deficiency. This condition should be examined with other parameters combination aswell as those influenced by diurnal variation and infection-inflammation condition. Reticulocyte hemoglobin (Ret-He) parameter canbe used as a marker of bone marrow iron availability because these reticulocytes are young erythrocytes released from the bone marrowinto the circulation. These conditions were circulated only within a short time about 1-2 days before becoming mature erythrocytes. Theaim of this study was to determine the Ret-He level diferentiation between absolute IDA and non absolute IDA states in ESRD patientswhom underwent maintenance hemodialysis. This research was conducted in the Laboratory of Clinical Pathology-RSHS-Bandung fromSeptember 2012 to June 2013. The study design was cross-sectional. All subjects were ESRD patients undergoing hemodialysis maintenancefor at least three (3) months and consisted of absolute IDA and non-absolute IDA based on the results of the ferritin and transferrinsaturation calculations according to the criteria of Pernefri 2011 Reticulocyte hemoglobin levels were checked using a fluorescenceflowcitometry principle in the automated hematology analyzer. In this study it was found that the Ret-He mean in the absolute IDA was26.1 pg/cell and 35.9 pg/cell in non absolute IDA. Statistical analysis was performed using Independent T-test. A total of 61 undergoingmaintenance hemodialysis subjects participating in this study comprised patients with absolute IDA and non-absolute IDA who met theinclusion and exclusion criteria. It can be concluded that the Ret-He level in statistical analysis showed absolute IDA which was meaningfullower than nonabsolute IDA in ESRD patients undergoing maintenance hemodialysis (p<0.001).